Marta o la lluna percudida. A propòsit d’una conversa poètica de Miquel Martí i Pol - Carbó, Ferran (Caplletra. Revista Internacional de Filologia, 1997)
This article deals with one of the most significant aspects of the poetry of Miquel Martí i Pol during a rich poetic period in the seventies, that is to say the strategy of undoubling which permits an apparent dialogue between the poet and anothe one. This resource is revised in one of the most republished books of the period, Estimada Marta, through the analysis of the formation of the alter ego Marta, which makes possible the celebration of the anniversary of illness and above all, through poetry, the exaltation of desire and imagination.